Wpływ zmian norm ostrożnościowych na konsolidację sektora bankowego w Polsce - Mleczko, Urszula (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The process of integration of financial markets including the banking sector requires creating uniform standards of action for these institutions. Referring to the banking sector creating these standards is one of the basic goals for the Basel Committee of Banks' Supervision, the EU, banks' supervision in particular countries and other international and national institutions. All these standards aim at making the financial turnover safe and the market mechanism - effective - due to the increased transparency and openness. Since the beginning of the process of transformation of the Polish economy circumspection regulations have been implemented. They have been an essential factor influencing changes, in particular the consolidations processes.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 325-336